2001
DOI: 10.1186/1471-2407-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Digitoxin medication and cancer; case control and internal dose-response studies

Abstract: Background: Digitoxin induces apoptosis in different human malignant cell lines in vitro. In this paper we investigated if patients taking digitoxin for cardiac disease have a different cancer incidence compared to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 19 publications
8
105
0
Order By: Relevance
“…The growing body of epidemiological (19,20), in vitro (18), and in vivo (31) evidence supporting the anticancer benefits of cardenolides has prompted the search for noncardioactive analogs that retain anticancer activity. The specific mechanism of cardenolide-induced cytotoxicity remains controversial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing body of epidemiological (19,20), in vitro (18), and in vivo (31) evidence supporting the anticancer benefits of cardenolides has prompted the search for noncardioactive analogs that retain anticancer activity. The specific mechanism of cardenolide-induced cytotoxicity remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its well known cardiac activity, which is mediated by inhibition of the plasma membrane Na ϩ ͞K ϩ -ATPase (17), digitoxin has demonstrated in vitro anticancer properties (18), and patient profiling suggests the survival rate of cancer patients taking digitoxin is statistically enhanced (19,20). Cardiac glycosides were also recently noted to inhibit the expression of four genes that are overexpressed in prostate cancer cells, including transcription factors and the apoptosis inhibitor survivin (21), and to provide protective effects against polyglutamine-based diseases (22).…”
mentioning
confidence: 99%
“…A review of plasma samples from 9271 cardiac patients revealed high concentrations of digitoxin were associated with a lower risk for leukemia, lymphoma and cancer of the urinary tract. 80 A number of in vitro studies have confirmed anti-cancer effects of digoxin and other glycosides (reviewed in 78,79). Based on these and other clinical and preclinical data, two trials involving digoxin have been initiated (Clinical Trials.gov NCT00281021 and NCT00650910).…”
Section: Discussionmentioning
confidence: 99%
“…Use of various medications, such as antibiotics (20)(21)(22), nonsteroidal anti-inflammatory drugs and other analgesics (20,(23)(24)(25), corticosteroids and other immunosuppressants (20,23,(26)(27)(28)(29), histamine2 receptor antagonists (30,31), psychotropic drugs (20,28,32), anticonvulsants (33)(34)(35), estrogen replacement therapy (20,36), antidepressants or antianxiety drugs (37,38), amphetamines (38), and digitalis or digitoxin (20,39), has been associated with risk of nonHodgkin's lymphoma (NHL). However, to our knowledge, there is very little information on medication use and subsequent risks of multiple myeloma or other lymphoproliferative malignancies.…”
Section: Introductionmentioning
confidence: 99%